Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Given a 2 + b 2 = c 2 , prove that log b+c a + log b-c a = 2log b+c a * log c-b a

Given a+ b= c2, prove that logb+ca + logb-ca = 2logb+ca * logc-ba

Grade:11

1 Answers

Ritesh Khatri
76 Points
3 years ago
 logb+ca + logb-ca
= 1/(logab+c) +1/(logab-c)
=(logab+c + logab-c)/(logab+c*logab-c)
=logab2-c2/(logab+c*logab-c)
=logaa2/(logab+c*logab-c)
=2/(logab+c*logab-c)
=2logb+ca * logc-ba

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free